Influence of the COVID-19 Pandemic on Quality of Life of Patients with Parkinson’s Disease - Dengjun Guo; Bing Han; Yuqiang Lu; Chenling Lv; Xiaoling Fang; Zhenzhong Zhang; Zhenguo Liu; Xiaoping Wang (Parkinson's Disease)
Introduction. This study investigated the influence of lockdown during the 2019 coronavirus disease (COVID-19) pandemic on the quality of life of patients with Parkinson’s disease (PD). Methods. We conducted a questionnaire survey involving 113 patients with PD from Xihu District, Hangzhou, Zhejiang. During the epidemic prevention and control period (February 1 to March 31, 2020), patients enrolled were asked to fill out questionnaires, including the “COVID-19 Questionnaire for PD Patients during the Period of Epidemic Prevention and Control” and “39-item Parkinson’s Disease Questionnaire (PDQ-39).” During the phase of gradual release of epidemic prevention and control (April 1 to April 30, 2020), all patients were followed up again, and PDQ-39 questionnaires were completed. Results. The quality of life for patients during the period of epidemic prevention and control was worse than that after epidemic prevention and control (P < 0.001). The biggest problem that they faced was that they could not receive their doctor’s advice or guidance regularly. The quality of life of patients who had difficulty getting doctors’ guidance or those who changed their routine medication due to lockdown was even worse. Telemedicine was quite effective and efficient for patients to get doctors’ guidance during lockdown. Conclusions. The inconvenient treatment during the pandemic directly caused the aggravation of patients’ symptoms and the decline in their quality of life. It is suggested that social media (such as WeChat or Tencent QQ) are used for regular interactions and follow-up appointments for patients with inconvenient medical treatment.